A Case of Transcranial Direct-Current Stimulation for Childhood Stroke Hemiparesis: A Brief Report. (17th February 2020) - Ciechanski, P; Carlson, HL; Herrero, M; Lane, C; MacMaster, FP; Kirton, A
ABSTRACT: Purpose : Survivors of childhood stroke incur lifelong physical disability. Treatment options are limited, however, models of motor reorganization after stroke are revealing cortical targets for neuromodulation. Transcranial direct-current stimulation (tDCS) enhances motor learning and may improve motor recovery in adult stroke, but remains uninvestigated in childhood-onset stroke. Here we documented the feasibility and safety of tDCS in an adolescent with chronic stroke-induced hemiparesis. Materials and methods : Over 10 days, the participant underwent occupational therapy paired with contralesional, primary motor cortex-targeting, cathodal tDCS. Clinical motor outcomes, and safety and tolerability measures were completed. Results : tDCS was well-tolerated with no adverse events. Motor outcomes did not regress post-intervention, with clinically significant changes still evident at 6 months. Conclusions : Application of controlled trials of non-invasive neuromodulation are safe and tolerability in childhood-onset stroke.